Neck circumference and metabolic syndrome - Merizalde, Dennys Leonardo Abril (2020)
Introduction: The presence of metabolic syndrome in patients with obesity is considered a public health problem in the world, since its diagnosis builds a pattern of several factors of cadiometabolic risk. Neck circumference (CCUE) is a new measurement that may be related to these risk factors. Objective: Analyzed the relationship between metabolic syndrome and CCUE in patients 40 to 64 years of age at the Nature Nutrition Center. Metodology: The study was descriptive, not experimental, transversal, with analytical method. The sample that was received was 78 patients treated in an outpatient clinic, women between 40 and 64 years.Cervical obesity is diagnosed in patients with a CCUE greater than 35cm. Results: A statistically significant relationship is evident between the CCUE with the abdominal circumference (r = 0.50 p = 0.00), BMI (r = 0.59 p = 0.00) and glucose (r = 0.39 p = 0.00). Conclusion: When analyzing the relationship between the presence of Metabolic Syndrome and CCUE, a positive relationship is determined between the indicators of the diagnosis of Metabolic Syndrome (abdominal perimeter and glucose) and the CCUE, therefore, the incorporation of this anthropometric measure into the anthropometric assessment of nutritional care in overweight and obese patients is recommended.